2(3x-2)2=6x-4

Simple and best practice solution for 2(3x-2)2=6x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-2)2=6x-4 equation:


Simplifying
2(3x + -2) * 2 = 6x + -4

Reorder the terms:
2(-2 + 3x) * 2 = 6x + -4

Reorder the terms for easier multiplication:
2 * 2(-2 + 3x) = 6x + -4

Multiply 2 * 2
4(-2 + 3x) = 6x + -4
(-2 * 4 + 3x * 4) = 6x + -4
(-8 + 12x) = 6x + -4

Reorder the terms:
-8 + 12x = -4 + 6x

Solving
-8 + 12x = -4 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + 12x + -6x = -4 + 6x + -6x

Combine like terms: 12x + -6x = 6x
-8 + 6x = -4 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + 6x = -4 + 0
-8 + 6x = -4

Add '8' to each side of the equation.
-8 + 8 + 6x = -4 + 8

Combine like terms: -8 + 8 = 0
0 + 6x = -4 + 8
6x = -4 + 8

Combine like terms: -4 + 8 = 4
6x = 4

Divide each side by '6'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| -20-5x=9x+22 | | (2x+1)(x+7)= | | 2y^2+25y-150=0 | | 1=5n | | (6x-15)(3x+20)=(5x-4)(8x+3)-(12+22x^2) | | 15n^2+8n-16=0 | | 4+20m+25m^2=0 | | 7+3m=34 | | 24+10m+m^2=0 | | (3-x)(5+x)-4x=(2-x)(8+x)-x | | y=6x^5-5x^4-30x^3+11x | | 3x^3-x^2+2x-24=0 | | (5x)(-7)+(8)=(6x)(-7)-(7) | | (x+2)(3-x)=(5+x)(7-x)+2(x+29) | | 4x+7y=2005 | | 4x+9y=58 | | 4(x-1)+3(2+x)=2 | | 20-4P=10+P | | 6x+28=52+x | | 4(2x+5)-10=-8+5x | | (12-x)(15+x)=(8-x)(9+x) | | (12-x)(15+x)=(8-x)(9+x) | | 5(x-1)-3(4x+2)=2(2x-1) | | x^4+6x^3+5x^2-12x+3=0 | | 5x-1=15-101 | | 3x+7=2(2x+10)-15 | | 40-2P=20+2P | | 5x^2+4x=3(2-x) | | 6x-3+4x+5=12 | | 0.5x-4=4 | | y=4x^2+3x^3 | | (x+2)(x-3)=x(x-2) |

Equations solver categories